APLIKASI QUIZ PENGENALAN INFORMASI TERKAIT WISATA PADA DINAS KEBUDAYAAN DAN PARIWISATA PROVINSI JAMBI: Quiz Application, Unity Jambi, Tourism, Interactive Education, Culture and Tourism - Simorangkir, Lucy; Nandra, Dwi (LP2M Universitas Nurdin Hamzah, 2025)
The Jambi Provincial Culture and Tourism Office, located in Kotabaru District, Jambi City, is the government agency responsible for regulating and implementing governmental matters related to culture and tourism in Jambi Province. The promotion of regional natural tourism still faces several challenges. This hinders the ability to obtain accurate information about tourist profiles and preferences for local tourism destinations. To minimize these obstacles in nature tourism promotion, a Unity application tool related to tourism and culinary needs was developed. This information application is expected to address the challenges faced by the Jambi Provincial Culture and Tourism Office. It allows tourists from various regions to more easily search for tourist attractions and culinary delights, providing deeper insight into the descriptions provided in the application. Furthermore, its integration with the C# programming language provides greater flexibility in modifying and developing analyses tailored to specific needs. The expected results of this application are that it will benefit the Jambi Provincial Culture and Tourism Office.